The Idea of Time and the Evolution of History. Thoughts on a Dialectic in Spanish Medieval Judaism - José Antonio Fernández López (Cauriensia)
From its origin, Israel has been determined by history. The Jewish people was shaped historically as such around the Torah. However, Jewish history itself witnessed in its bosom the birth of spiritual experiences that go beyond historical and chronological boundaries. Aside from history and temporality, some experiences, paradoxical to its collective existence, appear continuously in Jewish history throughout time. In the present article we will analyze, from the perspective of philosophy and theology of history, this duality in a time and place that are key to its understanding: The Middle Ages in the Iberian Peninsula. Our research is a transversal outlook in which this topic is addressed from a broad analysis ranging from tradition and scripture, to mystique, philosophy and eschatology.